2019
DOI: 10.15625/2525-2518/57/1/12903
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Potential of Five Compounds Extract From the Marine Fungus Aspergillus Flocculosus by DFT Method: Hat and Set Mechanism.

Abstract: Antioxidant potential of five compounds include ochraceopone F (1), aspertetranone D (2), cycloechinulin (3), wasabidienone E (4) and mactanamide (5) in the extracts from marine fungus Aspergillus flocculosus in Nha Trang was investigated by computational chemistry methods. All calculations were performed at the theoretical level M05-2X/6-311++G(d, p)//M05-2X/6-31+G(d) in the gas phase. The physicochemical properties such as bond dissociation energies (BDE), ionization energies (IE), electron affinity (EA) cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(14 reference statements)
0
0
0
Order By: Relevance
“…According to our previous investigation, crude extracts from marine fungal strains obtained from Nha Trang bay could reduce DPPH and ABTS free radicals with a proportion of 61.5% and 80.3%, respectively [14]. Interestingly, five antioxidant compounds such as ochraceopone F, aspertetranone D, cycloechinulin, wasabidienone E, and mactanamide were found in the spongederived fungus Aspergillus flocculosus from Nha Trang bay [15].…”
Section: Antioxidative Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…According to our previous investigation, crude extracts from marine fungal strains obtained from Nha Trang bay could reduce DPPH and ABTS free radicals with a proportion of 61.5% and 80.3%, respectively [14]. Interestingly, five antioxidant compounds such as ochraceopone F, aspertetranone D, cycloechinulin, wasabidienone E, and mactanamide were found in the spongederived fungus Aspergillus flocculosus from Nha Trang bay [15].…”
Section: Antioxidative Activitymentioning
confidence: 99%
“…Due to the increasing demand for new antibiotics mechanism of action, antibacterial activity is one of the looks of the properties of marine fungi [12,13]. Besides, recent studies have confirmed marine fungi are a valuable source of antioxidant compounds with potent biological activity and various structural features, promising sources of novel bioactive compounds [14,15]. Hence, in this study, we evaluated the potential antibiotic and antioxidant activities of marine fungi isolated during the field survey on the Akademik Oparin vessel in 2021.…”
Section: Introductionmentioning
confidence: 99%